Epistemological Foundations for Koons' Cosmological Argument? - Oppy, Graham (European journal for philosophy of religion, 2010)
Some peopleincluding the present authorhave proposed and defended alternative restricted causal principles that block Robert Koons new cosmological argument without undermining the intuition that causation is very close to ubiquitous. In Epistemological Foundations for the Cosmological Argument, Koons argues that any restricted causal principles that are insufficient for the purposes of his cosmological argument cause epistemological collapse into general scepticism. In this paper I argue, against Koons, that there is no reason to suppose that my favourite restricted causal principle precipitates epistemological collapse into general scepticism. If we impose the same kinds of restrictions on causal epistemological principles and on principles of general causation, then we cannot be vulnerable to the kind of argument that Koons develops.